OBRIST, Hans Ulrich. Uma breve história da curadoria. São Paulo: BEI Comunicação, 2010. - Corrêa, Ronaldo de Oliveira (ILUMINURAS, 2013)
OBRIST, Hans Ulrich. Uma breve história da curadoria. São Paulo: BEI Comunicação, 2010.